The experience of Islamization of Knowledge at the International Islamic University Malaysia: successes and challenges - Ssekamanya, Siraje Abdallah; Hussien, Suhailah; Ismail, Nik Ahmad Hisham (IIUM Press, 2011)
From its establishment in 1983, the International Islamic University Malaysia (IIUM) has been committed to the integration of Islamic values with the modern fields of knowledge. This constitutes the core of IIUM’s vision and mission. The purpose of this study was to analyze the experience of Islamization of knowledge at IIUM. It involved interviews with a total of eleven key scholars at IIUM who have been active in the Islamization of knowledge and in the management of the university. Interview data were supplemented by document analysis of course outlines university strategic planning documents, seminar and conference proceedings, as well as secondary literature. Contrary to the misgivings of many critics of the Islamization project, IIUM has scored several successes. Many areas still need to be improved though. Among the most important findings are those related to the quality and readiness of both the teachers and students to contribute to Islamization of knowledge in their research and publications. Future directions should include conducting research to find solutions for the problems facing Muslim societies in particular and humanity in general. Findings from those studies will be the basis for Islamized textbooks and other teaching materials.